Ecological studies in primary hill dipterocarp forest at Semangkok Forest Reserve, Selangor / Abd. Rahman Kassim … [et al.] - Kassim, Abd. Rahman; Niiyama, Kaoru; Ibrahim, Shamsuddin; Ripin, Aziz (2002)
A six-hectare ecological plot was established in 1992 to study the community structure and dynamics of major tree species in a primary hill dipterocarp at Semangkok Forest Reserve. The plot dimension was 200 x 300 m. The six-hectare plot were divided to 150 20 x 20 m quadrats and 2400 5 x 5 m sub-quadrats. All young and mature trees> 5 cm diameter-at-breast height (dbh) were tagged, mapped, measured and identified to species level. To date 5 recensus has been conducted. A sub-sampling of seedlings and saplings below 5 cm dbh were also collected. The main objective of the study was to clarify the life history of major species in primary hill dipterocarp forest. The paper presented findings on the species diversity, abundance and spatial pattern assessment from the last ten years of research.